Introduction to Naval Architecture (5th Edition) - Tupper, E. C. (Elsevier, 2013)
This book is the most well-known and trusted introduction to the principles affecting the design, construction and operation of marine vessels and structures. It offers a wide ranging yet clear and concise technical guide to the basics of this broad field, with minimal emphasis on complex equations and mathematics. Written by an award-winning naval architecture author, this new edition has been fully updated to cover recent advances and developments in naval architecture. It is ideal for students approaching the subject for the first time, experienced naval architects requiring an up-to-date reference, and other marine professionals needing a working knowledge of the area.